Lipase-catalyzed synthesis of kojic acid derivative in bioreactors and the analysis of its depigmenting and antioxidant activities - Lajis, Ahmad Firdaus; Hamid, Muhajir; Ahmad, Syahida; Ariff, Arbakariya (M D P I AG, 2017)
In this study, 7-O-kojic acid monopalmitate (7-O-KAP) was synthesized using palmitic acid and kojic acid where the yield and biological activities were analyzed. The highest yield of 7-O-KAP (43%) can be obtained at molar ratio of 1:1, enzyme loading of 5% (w/v), temperature of 70 °C, using immobilized lipase N435 in solvent-free system. Stirred tank reactor (STR) provides better mixing of the substrates and biocatalyst with better yield of 7-O-KAP, compared to fluidized tank reactor (FTR) and packed bed reactor (PBR). The 7-O-KAP exhibited pseudoplastic behavior with flow behavior index (n) being less than 1. The 7-O-KAP showed better depigmenting activity with the reduction of melanin content in Danio rerio embryo to 18.70%, significantly lower than the positive control, kojic acid (60.39%) at highest concentration tested (250 μg/mL). Intracellular tyrosinase in Danio rerio embryo was also reduced when treated with 7-O-KAP (12.53%), compared to kojic acid (37.36%) at concentration of 250 μg/mL. In FRAP assay, 7-O-KAP had antioxidant activity of 8156 AAE/mL, which was higher than kojic acid (6794 AAE/mL) at concentration of 2 mg/mL. The 7-O-KAP also reduced peroxidation activity to 12.21%, which was better compared to kojic acid (31.68%) at 2 mg/mL. Moreover, it was found that lipid peroxidation activity of 7-O-KAP (12.21%) was comparable to BHT (11.56%) at 2 mg/mL. Based on this study, 7-O-KAP could be an alternative compound for whitening agent and antioxidant compared to kojic acid and BHT, respectively